Genndy Tartakovsky Sincerity in Animation - Tembo, Kwasu David (Animation: Key Films/Filmmakers, 2022)
Genndy Tartakovsky is widely regarded as a pioneer in contemporary Western animation of the 20th and 21st centuries. His groundbreaking and prolific output, ranging from Dexter's Laboratory to Samurai Jack and Sym-Bionic Titan, has become a mainstay of contemporary animated programming, and collectively, the cornerstone of both titans of the industry such as Cartoon Network and Adult Swim. This open access book draws attention to the comparatively mysterious figure of this creator, while simultaneously celebrating his singular vision, mastery of formal technique, genre sensitivity, personal stylistic flair, and how these aesthetic and narrative elements combine to produce what the author calls an 'animation of sincerity' in all his works. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on www.bloomsburycollections.com.